WhatsApp and Telegram applied to journalism practice: A constant challenge for media. - Sedano, Jon; Palomo-Torres, María Bella (My University, 2023)
Instant messaging applications like WhatsApp and Telegram have become indispensable tools for proximal communication with audiences in today’s mobile society (Schwarz & Rupp, 2016). The attentive gaze directed by the media at audience habits has justified their incorporation (Westlund, 2013) and/or influence in journalistic routines, where they are employed as punctual or complementary solutions for both internal and external communication (Dodds, 2019).
Keywords: Redes sociales en Internet; Periodismo; Instant messaging apps; Journalism practice; Mobile journalism; Platform; Professional routines